Cross-industry applications of cyber security frameworks - Baral, Sukanta Kumar, 1966-; Goel, Richa, 1980-; Rahman, Md. Mashiur, 1980-; Sultan, Jahangir, 1956-; Jahan, Sarkar, 1979- (Advances in information security, privacy, and ethics (AISPE) book series., 2022)
"This book posits that rather than cybersecurity being simply an issue of securing systems and networks, corporate leaders need to think in terms of assuring the integrity and durability of the interconnected business and social structures that sit on top of an increasingly complex technology landscape"--